Production of Fatty Acid Methyl Ester Surfactants using Palm Oil with Various Reaction Temperatures and Duration - Agatha, Stefanie Bernike; Ariviani, Setyaningrum; Yuliatun, Simping (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Most surfactants are made from petrochemicals, posing significant environmental concerns due to the non- biodegradable and non-renewable nature. To address this challenge, surfactants from biodegradable, non-toxic, and harmless materials are required, such as Fatty Acid Methyl Ester (FAME) derived from palm oil. Therefore, this research aimed to investigate the effect of reaction tempetarures and durations as well as the interactions on the yield of FAME surfactants. The characteristics of the highest yield of FAME surfactants were also examined, including HLB (hydrophilic-lipophilic balance) value, surface tension, CMC (critical micelles concentration), density, and pH values. The study was conducted using Completely Randomized Factorial Design with three (3) factors, namely temperature (50 and 60 °C), reaction duration (60, 90, and 120 minutes), and the interaction. The results showed that the highest yield of 82.43% was produced at an interaction reaction temperature of 60 °C and a duration of 120 minutes. The characteristics of surfactants obtained were HLB value of 5.47, surface tension of 30.49 dyne/cm, capable of reducing surface tension by 73.20% (from 72.80 to 19.52 dyne/cm), CMC, density and pH values of 1.50% (v/v), 0.8757 g/cm 3 , and 6.86, respectively. These characteristics suggested that FAME has the potential for application as a water-in-oil (w/o) emulsifier. Moreover, the results could be applied to produce biodegradable surfactants using tropical oils through easy and simple technology.